AVAILABLE AGRICULTURAL AREAS AND OWNERSHIP STRUCTURE OF HOLDINGS IN THE REPUBLIC OF SERBIA - Trivić, Nada M (Economics of Agriculture, 2021)
The subject of research in this paper is the analysis and presentation of data on agricultural holdings, the structure of available and utilized area. The main goal is to determine and explain more comprehensively and in detail, by using appropriate methods, and based on available data, the condition of utilized agricultural area and its characteristics by utilization categories and ownership structure of holdings. The importance of this research arises from the fact that the results on utilized agricultural area can be used to adopt appropriate measures and undertake certain activities in land and overall agricultural and rural policy related to sustainable utilization, arrangement and protection of agricultural land and more balanced integrated development of rural areas, as well as to find better solutions in the field of utilization, ownership sector and conditions of agricultural area management.